Words on the move : why English won't and can't sit still (like, literally) - McWhorter, John H. (Henry Holt and Co., 2016)
"A bestselling linguist takes us on a lively tour of how the English language is evolving before our eyes and why we should embrace this transformation and not fight it. Language is always changing -- but we tend not to like it. We understand that new words must be created for new things, but the way English is spoken today rubs many of us the wrong way. Whether it's the use of literally to mean "figuratively" rather than "by the letter" or the way young people use LOL and like or business jargon like Whats the ask? it often seems as if the language is deteriorating before our eyes. But the truth is different and a lot less scary, as John McWhorter shows in this delightful and eye-opening exploration of how English has always been in motion and continues to evolve today. Drawing examples from everyday life and employing a generous helping of humor, he shows that these shifts are a natural process common to all languages, and that we should embrace and appreciate these changes, not condemn them. Words on the Move opens our eyes to the surprising backstories to the words and expressions we use every day. Did you know that silly once meant "blessed?" Or that ought was the original past tense of owe? Or that the suffixly in adverbs is actually a remnant of the word like? And have you ever wondered why some people from New Orleans sound as if they come from Brooklyn? McWhorter encourages us to marvel at the dynamism and resilience of the English language, and his book offers a lively journey through which we discover that words are ever on the move and our lives are all the richer for it"--